Experiences of Turkish Teachers Working Abroad - Çetin Toraman; Hasan Fehmi Özdemir; Şenol Orakcı (SAGE Open, 2020)
Turkish teachers seek to work abroad for a variety of reasons with a mixed degree of success. This study examined the common essence of the experiences of Turkish teachers, through 25 interviews with teachers commissioned to teach Turkish and Turkish culture to Turkish students in Germany and France. Interviews were conducted using semi-structured interview questions and audio recordings. The analyses used an appropriate content analysis process for a qualitative phenomenological approach. Krippendorff’s alpha coefficient showed high interrater reliability with a value of .83, and to ensure the credibility the codings have been submitted to internal and external checks. The direct quotations of the participants’ discourses were shared in the text. The results of the study showed that there was a particular driving force that directed teachers to teach abroad. This driving force embodied itself in a sense of curiosity and pride for being chosen to work abroad.